Penggalian Potensi Wisata Desa Kemlagi dalam Pengembangan Destinasi Wisata Kampung Tematik - Eny Rachmawati; Didit Panji Saputra; Risma Millatul Ummah; Bambang Wijanarko; Putri Diah Ayu Lestari; Ika Vitriasari; Bravo Chandra Arista; Mochamad Farizal; Mukhamad Agung Maulana; Kintan Puspita Wardani; Debrina Putri Buana; Nur Vina Yulfana; Putri Virda Rahayu; Faren Kesita Gelioni; Ervinda Hardina Dwi Pratiwi; Arvianti Pramudita Tjandra; Ricky Damara Paulus; Puput Anggraeni; Sintia Roseta Dela; Salwa Firdaus Syah; Bentar Putra Setiyanto; Adinda Putri Sari Rahayu; Fathurachman Samba; Elly Kurniawati; Muhammad Yunus; Vony Puspitasari (Universitas Maritim AMNI Semarang, 2025)
Village potential greatly influences the community's economy. Management of superior village products from various sectors will influence and provide beneficial impacts for the village itself. Kemlagi Village, Mojokerto Regency has various products in the tourism sub-sector based on culture/local wisdom, agriculture and livestock whose quality is not inferior to other potential villages. To increase the potential of the village area, it is necessary to increase the village branding of any potential sub-sectors that the village has. Therefore, it is carried out in several stages; field observations, interviews, documentation and data analysis related to village economic potential. With the result that the lack of public understanding of product marketing and promotion is the main obstacle in developing local potential. The community responded to this by providing suggestions and ideas to each other so that their village could develop. Apart from that, this activity also introduces the use of social media to help branding and promotion of villages and UMKM products in Kemlagi Village, Mojokerto Regency.